Pengembangan Model Bisnis Kolaboratif Eduplay Lolipop Playspace berbasis BMC dan CBMX untuk Mendukung Kesejahteraan dan Work–Life Balance Ibu Bekerja - Muadzah, Muadzah; Hakim, Cikita Berlian (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing number of working mothers has driven the need for support services that can balance the demands of work and caregiving. This study aims to analyze the contribution of eduplay services to the work-life balance (WLB) of working mothers and map the business models of service providers using the Business Model Canvas (BMC) and the Collaborative Business Model Matrix (CBMX). The research approach is qualitative and descriptive, using interviews with working mothers, eduplay managers, and direct observation. The results show that eduplay services play a significant role in improving WLB by providing safe, flexible, and educational play spaces, thereby reducing the burden of daily caregiving. The BMC analysis describes the value structure, operations, and customer relationships that strengthen the service's position. The CBMX integration highlights strategic collaborations between parents, local MSMEs, schools, government, and companies in creating a sustainable service ecosystem. This study confirms that a collaborative approach can strengthen the sustainability of MSMEs in the eduplay sector while providing social impacts for working families, especially mothers.